2010
DOI: 10.1017/s0022112009992606
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori study using a DNS database describing fluid disintegration and binary-species mixing under supercritical pressure: heptane and nitrogen

Abstract: A large eddy simulation (LES) a posteriori study is conducted for a temporal mixing layer which initially contains different species in the lower and upper streams and in which the initial pressure is larger than the critical pressure of either species. A vorticity perturbation, initially imposed, promotes roll-up and a double pairing of four initial spanwise vortices to reach a transitional state. The LES equations consist of the differential conservation equations coupled with a real-gas equation of state, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 56 publications
(122 reference statements)
0
26
1
Order By: Relevance
“…compared to employing the standard LES assumptions. These conclusions are different from those obtained for binary-species high-p mixing 13,14 and indicate that care should be taken not to infer properties of multi-species mixing from binary-species experiments.…”
contrasting
confidence: 81%
See 2 more Smart Citations
“…compared to employing the standard LES assumptions. These conclusions are different from those obtained for binary-species high-p mixing 13,14 and indicate that care should be taken not to infer properties of multi-species mixing from binary-species experiments.…”
contrasting
confidence: 81%
“…IV B; unclosed terms with significant activity are identified and modeled. Modeling of the conventional SGS fluxes is not addressed since previous studies have already evaluated, both in the a priori 12 and a posteriori 13,14 contexts, the accuracy of these SGS flux models (e.g., Smagorinsky model, gradient model, and self-similarity model) in the supercritical-p realm. Finally, the potential of the newly proposed models for the unconventional terms to increase the accuracy of LES for supercritical-p flows is determined through an a posteriori assessment.…”
Section: -3 G Borghesi and J Bellanmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this study, it is shown that entropy production rates in cryogenic injection are dominated by heat transport effects and not by viscous dissipation. Other researchers applied direct numerical simulations (DNS) [16] and large eddy simulations (LES) [17] to examine entropy generation rates in supercritical transitional mixing layers. The authors provided entropy production rates arising from viscous stress, species mass fluxes and heat fluxes and showed that the entropy production rates are fundamentally different from their subcritical counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…According to the scalar equation under supercritical conditions, [8][9][10][11][12] the transport equation of the SGS scalar variance is…”
Section: The Sgs Scalar Variance Transport Equationmentioning
confidence: 99%